Fast calculation of small-angle scattering profiles of dense protein solutions modeled at the all-atom level - Sanbo Qin; Huan-Xiang Zhou (Proceedings of the National Academy of Sciences, 2025)
The small-angle scattering (SAS) profile of a dense protein solution contains rich information about interprotein interactions, but extracting this information has been extremely challenging. In previous studies, we developed a fast Fourier transform-based method, FMAPB2, to compute protein pair interactions at the all-atom level. Here, we use FMAPB2 to precompute pair interaction energies and then use the latter to drive simulations of dense protein solutions. The resulting MAEPPI (many-protein atomistic energy from precomputed pair interaction) enables simulations of atomistic proteins at the speed of Lennard-Jones particles. On snapshots sampled from the simulations, we directly calculate the SAS profile. The results reveal artifacts generated by widely used spherical models and support a significant dimer population of bovine serum albumin at high concentrations. Our approach promises to modernize the prediction and interpretation of SAS profiles of dense protein solutions.